Customer satisfaction in Asia. Issue 6 (22nd April 2018) - Yi, Youjae; Nataraajan, Rajan
Abstract: Customer satisfaction is a key concept in modern marketing thought and practice, which emphasizes delivering satisfaction to customers and obtaining profits in return. Given the rapid growth of the markets in Asia, it is increasingly important to examine the applicability of customer satisfaction models and theories in Asian countries that have different economic and cultural characteristics compared to Western countries. This special issue thus brings together researchers from various disciplines interested in advancing customer satisfaction research in Asia. Brief descriptions of each of the seven articles featured in this issue are furnished. Collectively, these articles provide useful insights for those who wish to understand key factors for successful customer satisfaction management in Asia.